2022
DOI: 10.3390/polym14235173
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Possibilities of FDM Direct Colour Printing and Its Implications on Mechanical Properties and Surface Quality of the Resulting Parts

Abstract: The present paper aims to contribute to the methodology of 3D printing in-process colouring and study its implications and impact on the tensile strength and surface quality of the obtained parts. The proposed study was based on a Taguchi L27 DOE plan using standardised EN ISO 527-2 type 1B-shaped specimens, in which four factors on three levels were considered. The obtained results highlight the possibility of using the presented in-process colouring method. Different materials (PLA, PLA+, and PETG) with vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Other explanations for this phenomenon may be due to the increased adhesion between the layers due to the density changes of the test specimens, proven in the literature [ 43 , 44 ], where the authors concluded that by increasing the nozzle size, the density of the specimens also increases. Another explanation may be the fact that the wider the nozzle diameter, the longer the layers stay at a maintenance temperature that allows the material to settle better due to thermal convection [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other explanations for this phenomenon may be due to the increased adhesion between the layers due to the density changes of the test specimens, proven in the literature [ 43 , 44 ], where the authors concluded that by increasing the nozzle size, the density of the specimens also increases. Another explanation may be the fact that the wider the nozzle diameter, the longer the layers stay at a maintenance temperature that allows the material to settle better due to thermal convection [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that by increasing the nozzle diameter, the apparent density of the specimens changes, and significant voids appear in the internal structure of the specimens with sizes up to 254 µm when using 0.8 mm diameter nozzles. Moreover, in some cases, the material shows air pores due to nozzle wear or gas evacuation produced by filament moisture [ 34 ], leading to morphological changes in the material and, consequently, to the size and homogeneity of the specimen’s apparent section ( Figure 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response surface methodology (RSM) design of the experiment was employed to generate 30 different trial conditions (refer to Figure 1), each with 3 input parameter levels. Other factors such as material color and color percentage were neglected as these factors have a negligible effect on surface roughness [29]. The CAD model (refer to Figure 2) was sliced using Ultimaker Cura software to generate G-code.…”
Section: Methodsmentioning
confidence: 99%
“…The literature provides multiple studies that analyse the influence of printing conditions and parameters and post-processing methods on the mechanical properties of 3D-printed parts, especially FDM [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Several researchers have contributed with comprehensive reviews on these issues [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%